Negative hotel reviews on TripAdvisor: A cross-linguistic analysis. (April 2017) - Cenni, Irene; Goethals, Patrick
Highlights: Negative hotel reviews show more cross-linguistic similarities than divergences. 2.0 media platforms are laboratories for new and varied multilingual policies. Among the topics, the 'interpersonal' dimension shows most cross-linguistic divergence. Positive comments are more salient in English than in Italian or in Dutch. Abstract: In this empirical study, we investigate whether English-, Dutch- and Italian-written negative hotel reviews on TripAdvisor show similar or divergent characteristics. The main goal is to find out whether users writing in different languages constitute differentiated speech communities with different discursive norms or rather share the same norms and discourse habits. To answer this question, we examined 100 reviews for each language and analysed three features, namely the types of speech acts that they use, the specific topics that they evaluate and the extent to which they up-scale or down-scale their evaluative statements. The main conclusion of the cross-linguistic analysis is that there is a general trend towards similarity between the three language user groups under examination. We found analogous (although not identical) patterns for the three features. Within this overall trend towards similarity, specific divergences can be detected, for example regarding the status of positive comments in English-written reviews, or the status of the 'interpersonal' topic in Italian-written reviews.